Exploring the transcriptomic network of multi-ligand scavenger receptor Stabilin-1- and Stabilin-2-deficient liver sinusoidal endothelial cells - Olsavszky, Victor; Sticht, Carsten; Schmid, Christian David; Winkler, Manuel; Wohlfeil, Sebastian A.; Olsavszky, Ana; Schledzewski, Kai; Géraud, Cyrill; Goerdt, Sergij; Leibing, Thomas; Reiners-Koch, Philipp-Sebastian (Gene, 2021)
The Class H scavenger receptors Stabilin-1 (Stab1) and Stabilin-2 (Stab2) are two of the most highly expressed genes in liver sinusoidal endothelial cells (LSECs). While Stab1-deficient (Stab1KO) and Stab2-deficient (Stab2KO) mice are phenotypically unremarkable, Stab1/2-double-deficient (StabDKO) mice exhibit perisinusoidal liver fibrosis, glomerulofibrotic nephropathy and a reduced life expectancy. These conditions are caused by insufficiently scavenged circulating noxious blood factors. The effects of either Stab-single- or double-deficiency on LSEC differentiation and function, however, have not yet been thoroughly investigated. Therefore, we performed comprehensive transcriptomic analyses of primary LSECs from Stab1KO, Stab2KO and StabDKO mice. Microarray analysis revealed dysregulation of pathways and genes involved in established LSEC functions while sinusoidal endothelial marker gene expression was grossly unchanged. 82 genes were significantly altered in Stab1KO, 96 genes in Stab2KO and 238 genes in StabDKO compared with controls; 42 genes were found to be commonly dysregulated in all three groups and all of these genes were downregulated. These commonly downregulated genes (CDGs) were categorized as “potential scavengers,” “cell adhesion molecules,” “TGF-β/BMP-signaling” or “collagen and extracellular matrix (ECM) components”. Among CDGs, Colec10, Lumican and Decorin, were the most strongly down-regulated genes and the corresponding proteins impact on the interaction of LSECs with chemokines, ECM components and carbohydrate structures. Similarly, “chemokine signaling,” “cytokine-cytokine receptor interaction” and “ECM-receptor interaction,” were the GSEA categories which represented most of the downregulated genes in Stab1KO and Stab2KO LSECs. In summary, our data show that loss of a single Stabilin scavenger receptor - and to a greater extent of both receptors - profoundly alters the transcriptomic repertoire of LSECs. These alterations may affect LSEC-specific functions, especially interactions of LSECs with the ECM and during inflammation as well as clearance of the peripheral blood.
Gesehen am 20.11.2020